Nerium indicum, a botanical pesticide affects ultimobranchial gland of the catfish Heteropneustes fossilis. Issue 12 (24th August 2011) - Prasad, ManiRam; Kumar, Abhishek; Srivastav, Sunil Kumar; Srivastav, Ajai K.
<x xml:space="preserve">Abstract</x> Heteropneustes fossilis were subjected to 11.27 mg L−1 (80% of 96 h LC50) and 2.81 mg L−1 (20% of 96 h LC50) of Nerium indicum leaf extract for short‐term and long‐term, respectively. After sacrificing the fish, blood was collected on 24, 48, 72, and 96 h in short‐term and after 7, 14, 21, and 28 days in long‐term experiment and analyzed for plasma calcium levels. Also, ultimobranchial glands (UBG) were fixed on these intervals. Serum calcium levels of H. fossilis exhibited a decline after 48 h following exposure to Nerium indicum leaf extract. This decrease continued till the end of the experiment (96 h). Ultimobranchial cells exhibited a decrease in the cytoplasmic staining response after 72 h following the treatment. The nuclear volumes of these cells were slightly decreased. These changes were exaggerated after 96 h following the treatment. Chronically exposed fish exhibited a decline in serum calcium levels of H. fossilis on day 14. The level progressively declined till the end of the experiment. Up to day 14 following the treatment there was no change in the histological structure of UBG. A decrease in the nuclear volume of ultimobranchial cells was noticed on day 21. Moreover, the cytoplasm of these cells displayed weakstaining response. The nuclear volume of these cells recorded a further decrease following 28‐day treatment. Also there was noticed vacuolization and degeneration at certain places. To the best of our knowledge, the effects of any botanical pesticides on fish UBG have not been reported yet. © 2011 Wiley Periodicals, Inc. Environ Toxicol 28: 661–665, 2013.